Importância dos fragmentos de vegetação nativa para a manutenção do serviço de polinização no cultivo de soja - Costa, Rayssa Duarte (Universidade Federal de São Carlos, 2022)
The biotic pollination service is important for agriculture as it can provide an increase in quality, such as shape, flavor, durability, nutritional value and the number of fruits and seeds. Brazil stands out as the world's largest producer of soybean (Glycine max (L.) Merril), which, with the presence of pollinators, especially bees, can increase its production. In this work, we verified that biotic pollination helps in soybean production, in quantitative terms. To assess how much soybean productivity is dependent on pollinators, we applied, during flowering, two biotic pollination treatments in three crop areas with few differences between them (similar in surrounding vegetation cover, crop size, cultural practices/agronomic management, use of pesticides and fertilizers): treatment with the exclusion of biotic pollinators and control treatment, without the exclusion of pollinators, in the city of Leme, SP. The treatments were positioned at 50 m and 150 m from the edge of the forest fragment, and in duplicate. Transects were traced and were aided by pan traps to inventory the species of floral visitors present at the site. Biotic pollination increases the number and weight of seeds. Individuals in the control treatments showed higher productivity than the pollinator exclusion treatments. The distance of treatments in relation to the forest fragment did not present a significant difference for soybean productivity. Thus, we conclude that even though soybean is a predominantly autogamous species, productivity can be increased if the flowers were pollinated by biotic vectors.
Importance of forest fragments for maintenance of pollination service in soybean crop
Keywords: Fragmentos; Serviço ecossistêmico; Glycine max; Abelhas; Fragments; Ecosystem service; Bees; CIENCIAS AGRARIAS